2022
DOI: 10.1073/pnas.2119509119
|View full text |Cite
|
Sign up to set email alerts
|

Functional enzyme–polymer complexes

Abstract: Significance The use of biological enzyme catalysts could have huge ramifications for chemical industries. However, these enzymes are often inactive in nonbiological conditions, such as high temperatures, present in industrial settings. Here, we show that the enzyme PETase (polyethylene terephthalate [PET]), with potential application in plastic recycling, is stabilized at elevated temperature through complexation with random copolymers. We demonstrate this through simulations and experiments on diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…These two factors make attraction between like-charged macroions possible when a polyelectrolyte is bound to a protein on the wrong side of the isoelectric point. Meanwhile, the versatility of coacervation as a macro- or nano-encapsulation platform makes coacervates very attractive for industrial applications such as masking of flavors and oil [ 17 ], immobilization of enzymes [ 18 ], and controlled delivery of drugs [ 19 ], hormones [ 20 ] and angiogenic growth factors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two factors make attraction between like-charged macroions possible when a polyelectrolyte is bound to a protein on the wrong side of the isoelectric point. Meanwhile, the versatility of coacervation as a macro- or nano-encapsulation platform makes coacervates very attractive for industrial applications such as masking of flavors and oil [ 17 ], immobilization of enzymes [ 18 ], and controlled delivery of drugs [ 19 ], hormones [ 20 ] and angiogenic growth factors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been experimentally demonstrated that copolymers bearing groups that interact with the structure of the proteins through hydrophobic, polar and ionic interactions support the folding of membrane proteins in cell‐free synthesis, mimicking the work of chaperones [32] . Likewise, these polymers preserve the catalytic function of enzymes in organic solvents and elevated temperatures, showing stabilization far beyond that the one provided by PEGylated proteins [33] . Random copolymers also allow combining chemical functionalities in a single polymer in a forthright way [34] .…”
Section: Enzyme‐polymer Hybridsmentioning
confidence: 99%
“…In contrast, the conjugates with the nonresponsive linker showed no significant pH-dependent drug release. Waltmann et al 162 experimentally and theoretically demonstrated the application of protein−polymer complexes to plastic recycling at higher temperatures and demonstrated enhanced enzyme activity and stabilization at higher temperatures due to complexation with different random copolymers with the same backbone but polar, nonpolar, or charged side chains. Protein adsorption was found to be controlled by the number of contacts between polymer and proteins at different temperatures.…”
Section: Temperature-dependent Protein Binding and Adsorption On Trpsmentioning
confidence: 99%